THE ROLE OF NURSING IN THE ASSISTANCE OF PARTURIANT WHO SUFFER OBSTETRIC VIOLENCE: narrative review - Martins Cordeiro, Rafaela (2022)
Obstetric violence is characterized by aggressions suffered by the pregnant woman during the prenatal, delivery or postpartum period. In this context, the nurse plays a very important role in promoting a safe delivery, and its presence is essential when thinking about a humanized delivery. Nurses are the professionals trained in reception, generating well-being and comfort at the time of delivery. Aiming at approaching the theme, the general objective of this work was to verify how nurses are helped in cases of obstetric violence against women. As secondary objectives, one must understand what violence against women is, conceptualize obstetric violence and understand how nurses can help in this context. For this purpose, a narrative literature review was used as a methodological process, using Google Scholar, Latin American and Caribbean Literature on Health Sciences (LILACS) and the Scientific Electronic Library Online (SCIELO) virtual library on materials that addressed the topic.